2002
DOI: 10.1093/nar/gkf508
|View full text |Cite
|
Sign up to set email alerts
|

Predicted structure and phyletic distribution of the RNA-binding protein Hfq

Abstract: Hfq, a bacterial RNA-binding protein, was recently shown to contain the Sm1 motif, a characteristic of Sm and LSm proteins that function in RNA processing events in archaea and eukaryotes. In this report, comparative structural modeling was used to predict a three-dimensional structure of the Hfq core sequence. The predicted structure aligns with most major features of the Methanobacterium thermoautotrophicum LSm protein structure. Conserved residues in Hfq are positioned at the same structural locations respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
186
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 48 publications
4
186
0
Order By: Relevance
“…the welldocumented Hfq, have a role in the regulation of the expression of genes involved in virulence (Brennan & Link, 2007;Chao & Vogel, 2010; Christiansen et al, 2004;Vogel & Luisi, 2011). Of note, enterococci and streptococci do not harbour hfq-like genes (Sun et al, 2002).The aim of the present study was to further investigate the role of CspR in the virulence of E. faecalis. Interestingly, we observed that the addition of anti-CspR immune rabbit serum protected larvae of G. mellonella against killing by E. faecalis.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…the welldocumented Hfq, have a role in the regulation of the expression of genes involved in virulence (Brennan & Link, 2007;Chao & Vogel, 2010; Christiansen et al, 2004;Vogel & Luisi, 2011). Of note, enterococci and streptococci do not harbour hfq-like genes (Sun et al, 2002).The aim of the present study was to further investigate the role of CspR in the virulence of E. faecalis. Interestingly, we observed that the addition of anti-CspR immune rabbit serum protected larvae of G. mellonella against killing by E. faecalis.…”
mentioning
confidence: 86%
“…the welldocumented Hfq, have a role in the regulation of the expression of genes involved in virulence (Brennan & Link, 2007;Chao & Vogel, 2010; Christiansen et al, 2004;Vogel & Luisi, 2011). Of note, enterococci and streptococci do not harbour hfq-like genes (Sun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hfq shares sequence similarity to the eukaryotic Lsm proteins [23][24][25][26][27] We addressed these questions through a mutational analysis of Hfq, probing in vitro binding to several model RNAs that represent species with which Hfq must interact. Hfq mutants were assayed in vivo using a reporter assay and RNA lifetime experiments.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Hfq shares sequence similarity to the eukaryotic Lsm proteins [23][24][25][26][27] . In the Conserved Domain Database 28 Hfq is listed under the Sm and Sm-like protein family as well as among the eubacterial Hfqs.…”
mentioning
confidence: 99%
“…In 2002, a standard BLAST search identified Hfq in about half of the completed or nearly completed bacterial genomes (44). However, this standard BLAST search did not identify Hfq in cyanobacteria.…”
mentioning
confidence: 99%